Study on thermal and biodegradation resistance of tropical wood material composites - Sinin, Hamdan; Md. Saiful, Islam; Abu Saleh, Ahmed; Md. Rezaur, Rahman; Mohamad Rusop, Mahmood (John Wiley and Sons Inc., 2013)
Thermal stability and decay resistance properties of tropical wood polymer composites (WPCs) were investigated in this study. WPCs were prepared from several selected tropical wood species by impregnating the woods with methyl methacrylate (MMA) which was combined with a crosslinker, hexamethylene diisocyanate (HMDIC). The impregnation of wood with the monomer systems and polymerization were accomplished by vacuum-pressure method. Thermal properties of manufactured WPC in terms of thermogravimetric analysis and differential scanning calorimetry were evaluated, and an improvement in thermal stability was found for fabricated WPC. The wood was then exposed to two types of fungi; white-rot (polyporous versicolor) and brown-rot (postia placenta), for 12 weeks. Decay was assessed through percentage (%) of weight loss. A significant improvement was found in the treated woods compared to the untreated ones. The improvement in properties was observed as more potential with the MMA/HMDIC combination.